Semi-automated detection of ground monuments in airborne laser scan data - Maack Raun, Karl Hjalte; Volkmann, Armin ([KIT?], 2015)
LiDAR data provides a novel approach for locating and monitoring cultural heritage in the landscape, especially in areas of logistical complications, such as forests, rough terrain, and remote areas. However, the utilization of LiDAR presently lacks standardized and sustainable approaches for proper handling, developing, and processing within the field of archeology and cultural heritage management. Additionally a majority of stakeholders encounters various problems regarding macro- and micromanagement, often resolving in quantitative assessment being impractical or even impossible. Thus in order for LiDAR data to become a truly competent method for heritage management, a large scale quantitative and sustainable approach for handling, developing, and processing needs to be defined and established.
Gesehen am 07.07.2020
Conference Paper, September 2015
Conference: Data Life Cycle Lab “Key Technologies“, At KIT